Effects of temperature on cellulose hydrogen bonds during dissolution in ionic liquid. (1st December 2018) - Wei, Xiaoyi; Wang, Yihong; Li, Jihua; Wang, Fei; Chang, Gang; Fu, Tiaokun; Zhou, Wei
Highlights: Hydrogen bonds of cellulose might be cracked by two ways at different temperatures. The O(3)H–O(5) bonds disruption could promote the dissolution at lower temperature. The (O(2)H–O(6)) bonds might be responsible for dissolution at higher temperature. Higher dissolving temperature might be a way to avoid cellulose degradation in ILs. Abstract: Ionic liquids have been powerful solvents for cellulose. Mechanistic investigations of the dissolution processes have been extensively studied. In this paper, an experimental study has revealed that temperature also comes into play in cellulose dissolution. The supramolecular stuctrure of cellulose has been measured by X-ray diffraction, Fourier transform infrared spectroscopy, Solid-state CP/MAS 13 C NMR, X-ray photoelectron spectroscopy and Gel permeation chromatography analysis, and the effects of temperature on hydrogen bonds of cellulose in ILs were investigated. These results indicated that hydrogen bonds of cellulose might be cracked by different ways at different temperature: The disruption of intramolecular hydrogen bonds (O(3) H-O (5)) could promote the dissolution process at lower temperature. And the disruption of intramolecular hydrogen bonds (O(2) H-O (6)) might be responsible for cellulose dissolution at higher temperature. It was suggested that higher dissolving temperature might be a way to avoid cellulose degradation with a high cellulose yield.